IMPLEMENTASI PEMBELAJARAN ISMUBA UNTUK MENINGKATKAN PENGAMALAN RISALAH ISLAM BERKEMAJUAN DI PONDOK PESANTREN DARUL ARQAM MUHAMMADIYAH GOMBARA MAKASSAR - Ahmad, Ahmad; Bakri, Muhammad Ali; Bawa, Dahlan Lama (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
This research focuses on the implementation of ISMUBA (Islam, Muhammadiyah, and Arabic) learning at Darul Arqam Muhammadiyah Gombara Islamic Boarding School, Makassar, and its impact on improving the practice of progressive Islamic treatises. ISMUBA is a typical Muhammadiyah curriculum that integrates progressive Islamic values with mastery of Arabic, aiming to produce a young generation of faith, piety, and noble character. The research method used is descriptive qualitative, with phenomenological, theological, and pedagogical approaches. Data were obtained through observation, interviews, and documentation. The results show that the implementation of ISMUBA in the classroom involves structured learning and the use of diverse teaching methods, such as demonstrations of worship practices, role-play in Arabic, and Qur'an interpretation sessions. Learning outside the classroom includes visits to places of worship, Islamic social studies, and daily Arabic language practice. This study found that the implementation of ISMUBA at Darul Arqam Muhammadiyah Gombara Islamic Boarding School is effective in improving the practice of progressive Islamic treatises among students. This is shown through increased worship discipline, a deeper understanding of Islamic teachings, and better Arabic language skills. Challenges faced include limited resources and coordination, but can be overcome by increasing the number of qualified teachers and providing adequate learning facilities. The results of this study are expected to make a positive contribution to the development of learning models that are more effective and relevant to the needs of santri in this modern era.